"Paying it forward" via satisfying a basic human need: The need for relatedness satisfaction mediates gratitude and prosocial behavior. Issue 1 (21st February 2018) - Shiraki, Yuma; Igarashi, Tasuku
Abstract : People who receive kindness tend to feel gratitude and act in a prosocial manner toward third persons (i.e., "paying it forward"). Combining the separate evidence that (a) gratitude leads to the formation of strong psychological bonds from a beneficiary to a benefactor and that (b) people become more prosocial toward strangers when the need for relatedness (NFR) is satisfied, two online experiments were conducted to examine if NFR satisfaction mediates the association between gratitude and prosocial behavior toward third persons. After evoking gratitude by recalling past experiences (Study 1) or writing a letter to someone (Study 2), participants were asked to make a donation from their remuneration for the experiment to a charity organization. As predicted, emotional manipulation promoted donation via feelings of gratitude and satisfied NFR. Implications of the current model for integrating previous findings are discussed.